A pilot study of some aspects of the perceived usability of mobile advertising among students - Maja Rožman; Dijana Oreški; Polona Tominc (Naše gospodarstvo / Our Economy, 2022)
Abstract The pilot research is often intended to gather preliminary information and is usually based on a small set of observations to help decide how to conduct a more extensive study. The present pilot study is intended to provide preliminary results regarding various aspects of mobile advertising perceptions for young people. The objective of this pilot study is also to conduct the initial analysis of the relationships and impact of predecessors (influencing factors) on the attitudes towards mobile advertising and further on the perceived usefulness of mobile advertising among young people. Results show that the objectives of the pilot study have been fulfilled. They are crucial for continuing the main research on the importance of factors affecting the positive perception of the usefulness of mobile advertising among students and for designers of communication channels for the younger generation.
Keywords: A20; J10; 330; Mobile advertising; Pilot study; Students; Younger generation